Efficacy of the online Mindful Self-Compassion for Healthcare Communities program for surgical trainees: a prospective pilot study - Shin, Hyojung; Oh, Heung Kwon; Song, Yungsook; Kim, Yang Sun; Hur, Bo Yeon; Kim, Duck Woo; Kang, Sung Bum (Annals of Surgical Treatment and Research, 2023)
Purpose: The efficacy of the Mindful Self-Compassion (MSC) for Healthcare Communities program has not been verified. This study aims to evaluate the feasibility and efficacy of the online MSC for Healthcare Communities program on burnout, stress-related health, and resilience among surgical trainees. Methods: A single-arm pilot study was conducted at a tertiary referral academic hospital in Korea. Surgical trainees were recruited through flyer postings; therefore, a volunteer sample was used. Thus, 15 participants participated, among whom 9 were women and 11 were doctor-residents. The Self-Compassion for Healthcare Communities (SCHC) program was conducted from September to October 2021 via weekly online meetings (1 hour) for 6 weeks. The efficacy of the program was evaluated using validated scales for burnout, stress, anxiety, depression, self-compassion, and resilience before and after the intervention and 1 month later. Results: The results showed significantly reduced burnout, anxiety, and stress scores. After the program, high emotional exhaustion and depersonalization rates decreased, and personal accomplishment increased. Eight participants showed reduced anxiety postintervention, and 9 showed reduced stress. Improvements were observed between pre- and postintervention in resilience, life satisfaction, and common humanity. Changes in self-compassion predicted higher gains in resilience and greater reductions in burnout and stress. Conclusion: The SCHC is a feasible and effective program to improve resilience, self-compassion, and life satisfaction and reduce stress, anxiety, depression, and burnout in surgical trainees. This study highlights the need to include specific mental health programs in surgical training to improve trainees’ well-being.
Keywords: Mental health; Psychological burout; Self-compassion; Surgical trainee